Contribution of parental and school personnel smoking to health risk behaviours among Finnish adolescents - Jokela Jukka; Luopa Pauliina; Kivimäki Mika; Pietikäinen Minna; Virtanen Marianna; Elovainio Marko; Vahtera Jussi (BMC, 2009)
Abstract Background This study compared parental smoking with school personnel smoking in relation to adolescents' smoking behaviours, alcohol use, and illicit drug use. Methods A cross-sectional survey for 24,379 adolescents was linked to a survey for 1946 school employees in 136 Finnish schools in 2004-2005. Surveys included smoking prevalence reported by school staff, adolescents' reports of school staff and parental smoking, adolescents' own smoking behaviours, alcohol use, and illicit drug use. Multilevel analyses were adjusted for individual and school-level confounding factors. Results Parental smoking was associated with all health risk behaviours among both sexes (risk range 1.39 to 1.95 for other outcomes; Odds Ratio OR for smoking cessation 0.64, 95% Confidence Interval CI: 0.57, 0.72 among boys, 0.72; 0.64, 0.81 among girls). Among boys, high vs. low smoking prevalence among school personnel was associated with higher probability of smoking (OR 1.19; 95% CI 1.01,1.41), higher frequency of smoking during school time (Cumulative Odds Ratio COR 1.81; 95% CI 1.32, 2.48), frequent alcohol use (OR 1.23; 95% CI 1.01, 1.50), illicit drug use (OR 1.40; 95% CI 1.16, 1.69), and higher odds of reporting adults smoking at school (COR 1.51; 95% CI 1.09, 2.09). Among girls, high smoking prevalence among school personnel was related to higher odds of smoking (OR 1.18; 95% CI 1.02, 1.37) and lower odds of smoking cessation (OR 0.84; 95% CI 0.72, 0.99). Conclusion Parental smoking and school personnel smoking are both associated with adolescents' health risk behaviours but the association of parental smoking seems to be stronger.